2020
DOI: 10.21203/rs.2.20433/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Higher Prevalence of Obesity among Children with Functional Abdominal Pain Disorders

Abstract: Background Functional abdominal pain (FAP) disorders are one of the most common gastrointestinal disorders in children. We aimed to define the association between obesity and functional abdominal pain (FAP) disorders and to assess differences between overweight/obese children and normal weight children with FAP disorders. Methods We conducted a retrospective study of children (2-18 years old) with a clinical diagnosis of FAP who were followed-up in our pediatric gastroenterology unit between 1/2016-10/2018.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 29 publications
0
8
1
Order By: Relevance
“…Our findings seem to contradict the results of previous studies based at a medical clinic level that found an increased prevalence of FAPDs in obese children [ 7 ]. However, this contradiction may only be apparent as the design of previous studies made them prone to selection bias by only including children seeking medical care.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our findings seem to contradict the results of previous studies based at a medical clinic level that found an increased prevalence of FAPDs in obese children [ 7 ]. However, this contradiction may only be apparent as the design of previous studies made them prone to selection bias by only including children seeking medical care.…”
Section: Discussioncontrasting
confidence: 99%
“…Nevertheless, we cannot ignore the results of previous studies that found obese patients presenting to clinics were more likely to have FAPDs [ 7 ], and that obese patients had more prolonged, severe symptoms [ 13 ]. Together, the results of the current and previous studies seem to suggest that although obesity is not associated with higher rates of FAPDs at the community level, it may be an identifier for a more aggressive phenotype of FAPDs in children.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In our current study, diarrhoea, considered one of the ‘classic’ symptoms of CD and a typical expression of malabsorption, was more common among the overweight children. One possible explanation for the coexistence of these findings lies in an unbalanced fat‐rich diet being followed by these youngsters, in addition to a high incidence of functional diarrhoea and irritable bowel syndrome 21,22 . Another possible explanation concerns the low index of suspicion of CD: the diagnosis is usually considered only when the children present with a ‘classic’ symptom of the disease.…”
Section: Discussionmentioning
confidence: 99%